On the Inverse of a Square Matrix Using Logarithm - Rellon, Louie Resti (Indonesian Journal of Mathematics and Applications, 2023)
Assume that A is an n n matrix with real numbers as entries and the determinant of A ≠ 0. In this study, we established the results of getting the inverse of a matrix A using the logarithmic method and used some examples to discuss the necessity of getting the inverse of a matrix using the logarithm for both positive and negative determinants in terms of a given determinant of a matrix A. If the det A > 0, we have , where . However, if the det A < 0, we have , where .